Wykorzystanie nowoczesnych koncepcji zarządzania w działalności innowacyjnej przedsiębiorstwa - Miczyńska-Kowalska, Maria (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
XXI-century enterprises function in variable environment. Due to it, they must be more adaptable. The aim of this article is presentation some of the modern methods of management (TQM, reengineering, benchmarking) as an effective means of decreasing economic risk of functioning of enterprises, especially in preparation of production. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1086, s. 183-191